José de Escovar at the Chapel of the Souls: Technical and Material Study of a 1603 Panel Painting - Gil, Milene (2017)
This article reports the preliminary results of a technical and material study carried out on a 17th century panel painting located at the Chapel of the Souls in the main church of Vila Nova da Baronia (30 km away from Evora city, in southern Portugal). This painting is attributed to Jose the Escovar, a painter that worked for Evora Archiepiscopate between 1583 and 1622. Jose the Escovar is known by his mural paintings all across the Alentejo region. This is the first time that a panel painting made by this artist was studied. Analytical methods used included in situ technical photography (visible (Vis), raking light (RAK), infrared (IR), and ultraviolet (UV)), optical microscopy of cross sections, scanning electron microscopy with energy dispersive X-ray spectrometry (SEM-EDS), micro Raman spectroscopy, and micro Fourier transform infrared spectroscopy (m-FT-IR). The goal was to ascertain the techniques and colored materials used by Escovar on this painting so that the data can be used in future comparisons with others works attributed to this painter based on stylistic aspects.